2002
DOI: 10.1038/nn921
|View full text |Cite
|
Sign up to set email alerts
|

Transient neural activity in human parietal cortex during spatial attention shifts

Abstract: Observers viewing a complex visual scene selectively attend to relevant locations or objects and ignore irrelevant ones. Selective attention to an object enhances its neural representation in extrastriate cortex, compared with those of unattended objects, via top-down attentional control signals. The posterior parietal cortex is centrally involved in this control of spatial attention. We examined brain activity during attention shifts using rapid, event-related fMRI of human observers as they covertly shifted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

103
478
6
3

Year Published

2003
2003
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 626 publications
(590 citation statements)
references
References 43 publications
103
478
6
3
Order By: Relevance
“…Dimension changes further elicited activation along the descending and horizontal segments of the intraparietal sulcus, whereas response changes led to activation in its ascending segment. This distribution is in good agreement with studies of visual attention shifts, both between locations and between features, which have consistently reported activation along the horizontal segment of the intraparietal sulcus (Corbetta et al, 1998;Gitelman et al, 1999;Lepsien and Pollmann, 2002;Liu et al, 2003;Pollmann and von Cramon, 2000;Pollmann et al, 2000b;Weidner et al, 2002;Yantis et al, 2003), and with studies of prehensile movements (Binkofski et al, 1998(Binkofski et al, , 1999; and it is consistent with studies of motor attention (Rushworth et al, 2001), which have reported activation along the ascending segment of the intraparietal sulcus and functional deficits following natural lesions or transcranial magnetic stimulation of this segment.…”
Section: Dimension Changesupporting
confidence: 88%
“…Dimension changes further elicited activation along the descending and horizontal segments of the intraparietal sulcus, whereas response changes led to activation in its ascending segment. This distribution is in good agreement with studies of visual attention shifts, both between locations and between features, which have consistently reported activation along the horizontal segment of the intraparietal sulcus (Corbetta et al, 1998;Gitelman et al, 1999;Lepsien and Pollmann, 2002;Liu et al, 2003;Pollmann and von Cramon, 2000;Pollmann et al, 2000b;Weidner et al, 2002;Yantis et al, 2003), and with studies of prehensile movements (Binkofski et al, 1998(Binkofski et al, , 1999; and it is consistent with studies of motor attention (Rushworth et al, 2001), which have reported activation along the ascending segment of the intraparietal sulcus and functional deficits following natural lesions or transcranial magnetic stimulation of this segment.…”
Section: Dimension Changesupporting
confidence: 88%
“…Similar parietal and frontal regions also showed sustained increase of activity in a study that requires subjects to covertly track a small dot appearing at different locations in the visual periphery (Beauchamp et al, 2001). In an object-based visual attention task, transient activity during shifts of attention between objects were found in frontal and superior parietal regions (Serences et al, 2004); functionally similar parietal areas were also found in previous studies of spatial attention shifts (Vandenberghe et al, 2001;Yantis et al, 2002). Since the demand for attention shifting and maintenance of attention differs from task to task, it's possible that parietal and frontal regions engage in both the initiation and the maintenance of attention depending on the task demand.…”
Section: The Possible Sources and Mechanisms Of Attentional Modulationsupporting
confidence: 73%
“…Previous fMRI studies on dimension changes found significant activation of multiple posterior brain areas (e.g., Pollmann et al, 2000: fusiform gyrus, lateral occipital gyrus, superior/middle temporal gyrus, SPL and precuneus; Pollmann et al, 2006: IPS, fusiform gyrus, striate/peristriate cortex and posterior putamen/claustrum) that have been implicated in early attentional processes (Corbetta et al, 1993(Corbetta et al, , 1995(Corbetta et al, , 2000Corbetta & Shulman, 1999;Kelley et al, 2008;Macaluso et al, 2000;Nobre et al, 1997, Vandenberghe et al, 2000Yantis et al, 2002). Hence, it was concluded that dimension changes interfere with attention shifts to the target.…”
Section: Theoretical Implicationsmentioning
confidence: 99%